2020
DOI: 10.1371/journal.pone.0230580
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome assembly of four organs of Collichthys lucidus and identification of genes involved in sex determination and reproduction

Abstract: The spinyhead croaker (Collichthys lucidus) is a commercially important fish species, which is mainly distributed in the coastal regions of China. However, little is known about the molecular regulatory mechanism underlying reproduction in C. lucidus. A de novo transcriptome assembly in brain, liver, ovary and testis tissues of C. lucidus was performed. Illumina sequencing generated 60,322,004, 57,044,284, 60,867,978 and 57,087,688 clean reads from brain, liver, ovary and testis tissues of C. lucidus, respecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…To understand the expression patterns of DE-miRNAs, hierarchical clustering of DE-miRNAs was performed using Cluster 3.0. The target genes of each DE-miRNA were predicted via the analysis of differentially expressed genes between the ovaries and testes from the results of previous de novo transcriptome sequencing (Song et al, 2020). In brief, the 3′-UTR sequences of C. lucidus mRNAs were determined by the results of the de novo transcriptomes.…”
Section: Analysis Of De-mirnas and Target Gene Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the expression patterns of DE-miRNAs, hierarchical clustering of DE-miRNAs was performed using Cluster 3.0. The target genes of each DE-miRNA were predicted via the analysis of differentially expressed genes between the ovaries and testes from the results of previous de novo transcriptome sequencing (Song et al, 2020). In brief, the 3′-UTR sequences of C. lucidus mRNAs were determined by the results of the de novo transcriptomes.…”
Section: Analysis Of De-mirnas and Target Gene Predictionmentioning
confidence: 99%
“…As a result, to ensure a stable C. lucidus population, it is essential to elucidate the molecular mechanisms underlying reproduction and sex differentiation in this species. A previous study revealed that 333 and 556 unigenes were specifically expressed in the ovaries and testes, respectively, via de novo transcriptome sequencing of C. lucidus, and hyal, sycp3, and bmp15 might play an important role in reproduction and sex determination (Song et al, 2020). Furthermore, Li et al (2019) illustrated that vasa was highly conserved in C. lucidus and may take part in germ cell development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, large-scale artificial reproduction is imperative to compensate for the limited natural reproductive rate. Nevertheless, research on C. lucidus is mainly limited to morphology, immune-related gene identification, population genetics, genome assembly, and transcriptome assembly with few reports on sex determination [ 29 , 31 , 32 , 33 , 34 , 35 , 36 ]. In the previous study, C. lucidus germ cells marker gene vasa was isolated by us [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial genome maps of spiny head croaker and candidate genes related to its sex determination have been examined by mitochondrial genome sequencing ( Cheng et al, 2012b ), chromosome assembly ( Cai et al, 2019 ), and RNA sequencing ( Song et al, 2020 ). However, the genetic basis of well-developed otoliths in Sciaenidae species is still unknown.…”
Section: Introductionmentioning
confidence: 99%